I Increasing Satisfaction and Repurchase Intention on Contemporary Food and Beverages Through E-commerce: - - Subekti, Rini; Viana Praningtyas, Elisabeth Ria; Anggya Anggraini, Putu Ayu (Terbuka Journal of Economics and Business, 2023)
This study aims to analyze consumption behavior using 2 categories of consumer behavior, namely utilitarian shopping value and hedonic shopping value. Utilitarian shopping value and hedonic shopping value to increase satisfaction and repurchase intention in the contemporary food and beverage business through e-commerce. Nowadays, food and drink are not only basic needs but also a part of a lifestyle. The food industry is currently growing rapidly. According to data from the Ministry of Industry, the food and beverage industry is one of the important sectors that supports the performance of the non-oil and gas processing industry. In addition, the food and beverage industry is one of the sectors that receive development priorities according to the Making Indonesia 4.0 roadmap. Food and beverage products in great demand are various processed drinks made from coffee or tea, korean snacks, and others. These food and beverage products are also easy to obtain by purchasing online. Therefore, this condition becomes something interesting to observe, especially on consumer behavior. This research is quantitative analsys. This research using SEM PLS. The result of this study shows that hedonic shopping value, utilitarian shopping value, and satisfaction influences repurchase intention on an online contemporary foods and beverages. The biggest influence on the repurchase intention of contemporary food and beverages is hedonic shopping value. This study develops previous research, but in this study, it covers many food and beverage products. Respondents in this study were also from all over Indonesia.